2013
DOI: 10.1111/acel.12117
|View full text |Cite
|
Sign up to set email alerts
|

DGCR8-mediated disruption of miRNA biogenesis induces cellular senescence in primary fibroblasts

Abstract: SummaryThe regulation of gene expression by microRNAs (miRNAs) is critical for normal development and physiology. Conversely, miRNA function is frequently impaired in cancer, and other pathologies, either by aberrant expression of individual miRNAs or dysregulation of miRNA synthesis. Here, we have investigated the impact of global disruption of miRNA biogenesis in primary fibroblasts of human or murine origin, through the knockdown of DGCR8, an essential mediator of the synthesis of canonical miRNAs. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Loss of miRNA synthesis through blocking DGCR8 expression in adult C. elegans showed accelerated aging and reduced lifespan [57]. Knockdown of DGCR8 triggered a dramatic antiproliferative response and consequently senescence phenotype characterized by upregulation of p21 in primary fibroblasts of human and mouse origin [58]. In addition, several senescence regulating proteins are reported to regulate DGCR8.…”
Section: Changes Of Mirna Biogenesis During Aging and Cellular Senmentioning
confidence: 99%
“…Loss of miRNA synthesis through blocking DGCR8 expression in adult C. elegans showed accelerated aging and reduced lifespan [57]. Knockdown of DGCR8 triggered a dramatic antiproliferative response and consequently senescence phenotype characterized by upregulation of p21 in primary fibroblasts of human and mouse origin [58]. In addition, several senescence regulating proteins are reported to regulate DGCR8.…”
Section: Changes Of Mirna Biogenesis During Aging and Cellular Senmentioning
confidence: 99%
“…P53 was also shown to be a downstream target of miR-19b (Fan et al, 2014). MiR-21 may target p21, as it has been shown to reverse the effects of a deletion of DGCR8, the Drosha auxiliary protein, which usually leads to senescence (Gómez-Cabello et al, 2013). Details of miRNAs related to p53 are given in Table 1.…”
Section: Mirna Synthesis/actionmentioning
confidence: 99%
“…During senescence, various tumor suppressors and death signals inhibit many of the normal functions of the cell. Common tumor suppressor systems such as p53, p21, and p16 are regulated by miRNA expression (Borgdorff et al, 2010; Gómez-Cabello et al, 2013; Overhoff et al, 2014; Ugalde et al, 2011; Yamakuchi et al, 2008). The role of miRNAs in modulating the expression of pathways leading to cellular senescence has led to an increased focus on their role in induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…It is cleaved in the nucleus by the microprocessor complex (consisting of the RNase III endonuclease Drosha and the co-factor DGCR8. Recently it has been reported that knockdown of DGCR8 in primary fibroblasts induced senescent phenotype (Gómez-Cabello et al, 2013). Yet another contemporary study revealed that targeted inhibition of DGCR8 remarkably reduced migratory and invasive potential of ovarian cancer cells .…”
Section: Introductionmentioning
confidence: 99%